Helicobacter pylori presente no biofilme dental como fonte de reinfecção da mucosa gástrica - Gomes, Raquel Christina Barboza (2006)
It was aimed in the present work (i) to diagnose the presence of Helicobacter pylori on biofilm in dyspeptic patients, by estimating its prevalence; (i) to observe the concomitant action of systemic treatment and basic periodontal treatment for eradicating this microorganism in the gastric mucosa of mouth- and stomach-positive patients, by comparing with eradication obtained in stomach-positive patients; (ii) to evaluate the action of basic periodontal treatment of this bacterium in patient only infecting the mouth; (iii) as well to evaluate the action of systemic treatment of this bacterium in patient infected in the stomach. Buccal exams were performed in 123 patients and collection of samples was carried out from dental biofilm and gastric mucosa, through Upper Digestive Endoscopy. From the samples collected, DNA was extracted and sequencing reaction was performed in PCR − polymerase chain reaction. After confirming the presence of H. pylori, the patients were divided into Groups as follows: Group I, composed of 19 patients with H. pylori in the gastric mucosa and dental biofilm, 16 of them Were treated; Group II, composed of 14 patients with H. pylori only on dental biofilm, eite of them were treated; Group III, composed of 47 patients with H. pylori only in the gastric mucosa, 23 of them were treated; and Group III, composed of 43 patients not infected with this bacterium. The patients of Groups I and II received odontological treatment for eradicating H. pylori on dental biofilm. Patients of Groups I and III received systemic treatment for the eradication of H. pylori in the gastric mucosa. The results obtained were: the presence of Helicobacter pylori on biofilm in dyspeptic patients were19,51% for al the Groups, and 33,75% for the patients infected in the mouth and stomach; in Groups I and II only one patient from each group did not have H. pylori eradicated from the dental film after periodontal treatment, corresponding of 6,2% and 12,5%, respectively; in Groups I and III, four (25%) and three (13%) patients did not succeed, respectively, with respect to systemic therapy with Pyloripac-Lansoprazol 30 mg (one capsule), Clarithromycin 500 mg (one capsule), Amoxicillin (trihydrated) 500 mg (two capsules). The medicament was taken half an hour before breakfast and as the case might be half an hour before dinner. It was concluded that: (a) H. pylori presented low prevalence in the buccal cavity; (b) patients infected with H. pylori in the buccal cavity and gastric mucosa, after basic periodontal treatment showed similar levels of eradication of H. pylori, as compared to patients infected and with treatment applied only to their gastric mucosa. (c) the basic periodontal treatment showed to be effective for eradicating H. pylori on biofilm.